1996
DOI: 10.1016/0735-1097(95)00598-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro flow experiments for determination of optimal geometry of total cavopulmonary connection for surgical repair of children with functional single ventricle

Abstract: The results strongly suggest the incorporation of caval offsets in future total cavopulmonary connections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 9 publications
2
108
0
Order By: Relevance
“…Conserving as much as possible the mechanical energy of blood that flows through the connection is of crucial importance, considering that the single ventriele is respon sible fo r both the systemic and the pulmonary circulation. As a result, the fluid mechanical optimization of the TCPC has becn invcstigated through several in vitro, numerical and in vivo studi es [5][6][7][8][9][10][11][12][13][14][15][16][17][18], leading to improvements in the connection between thc caval and pulmonary vessels .…”
Section: Introductionmentioning
confidence: 99%
“…Conserving as much as possible the mechanical energy of blood that flows through the connection is of crucial importance, considering that the single ventriele is respon sible fo r both the systemic and the pulmonary circulation. As a result, the fluid mechanical optimization of the TCPC has becn invcstigated through several in vitro, numerical and in vivo studi es [5][6][7][8][9][10][11][12][13][14][15][16][17][18], leading to improvements in the connection between thc caval and pulmonary vessels .…”
Section: Introductionmentioning
confidence: 99%
“…In our in vitro experiments we studied three different designs of the TCPC with quantitative assessment of energy losses and correlated the losses with flow visual ization [7,10,11]. This gave information regarding con nections that would conserve energy and those that were particularly detrimental in this regard.…”
mentioning
confidence: 99%
“…On the basis of the results of those experiments, they advocated the use of TCPC that was designed to produce a more streamlined flow pattern that should lead to less energy loss. Subsequent in vitro 7,[17][18][19][20][21] and computational 8,18,19 studies confirmed those observations. The effect of progressive right atrial dilatation on energy loss and resistance to flow was recently studied by Lardo and associates 20 in an in vitro flow model of explanted sheep hearts with APA-type Fontan pathways.…”
Section: Discussionmentioning
confidence: 56%
“…To date, however, nonrandomized clinical studies comparing outcome for APA versus TCPC have yielded equivocal results. 4,5 Recent studies performed on in vitro models 7 and computer-based simulations 8 demonstrated that energy loss is greater and flow is more disturbed in Fontan circulation with APA compared with TCPC. These in vitro studies, however, may not accurately reflect in vivo conditions, and any differences between APA and TCPC pathways in this regard still remain unknown.…”
mentioning
confidence: 99%